Modern Mass Media as Instrument of Political Socialization of Youth - Natalya Valentinovna Gorbatova; Alexander Aleksandrovich Malkevich (Управленческое консультирование)
The article focuses on the role of the media in the process of political socialization of young citizens of Russia. Based on the data of sociological surveys in different years, the authors analyze the degree of influence of the media on the minds of young people and estimate the factors affecting the absorption of media information.Also, there is an attempt to understand the limits of the influence of media. This article examines the relationship of processes of political socialization and political identity, and identify the direct and indirect impact of the media on these processes.